PERAN PENASEHAT AKADEMIK TERHADAP KESUKSESAN MAHASISWA DI PERGURUAN TINGGI - Anidar, Jum (Institut Agama Islam Negeri Imam Bonjol Padang, 2012)
There are three aspects that make students become successfull: academic, carrier planning, and social relationship. The supervisor is person who take responsibility to assist the students in overcoming their problems. The supervisorâs tasks are to: a) provide a consideration to the students in chosing their subjects in certain semester, b) supervise and advise the students to gain their optimal learning achievement, c) give the explanation and direction about their study, d) give warning to poor students, e) observe humansâ behaviour, f) provide sufficient time for students to consult in campus, g) sign the studentsâ study planning cards (SSPC), h) examine and sign the extracurricular credit semester (ECS).